Architect’s computer applications in professional practice – How architecture education is complying to the needs of the market - M.F. Irfan Mohd Nor; I.M.S. Usman; M.M. Tahir; Che-Ani A.I (Penerbit UKM, 2008)
For the past 15 years, the architecture world has been supported greatly by the usage of Computer Aided Design (CAD) application, be it as a drafting tool or a design counterpart. Due to this, more and more CAD application tools have been developed and created to accommodate the demands of the market over the years. As the usage of CAD among architect firms becomes imminent, higher-learning institutions have taken a big role in preparing the design and construction market with workforce that is equipped with the necessary skills and ability to operate CAD. This paper aims to look into the insight of how higher learning institutions are keeping up with equipping their graduates with the right CAD applications that will be used in the workforce. The approach is by conducting a survey within 25 architecture firms of various sizes within Kuala Lumpur, the capital and largest city in Malaysia, to find out the actual CAD application tools used by them. The findings from this survey will then be counter checked with the tools/software taught in the higher-learning institutions as to know whether these institutions are equipping their graduates with the skills to operate the right CAD tools used in the workforce